Debt Sustainability Analyses for Low-Income Countries : An Assessment of Projection Performance - Mooney, Henry (IMF Working Papers; Working Paper ;, 2017)
This paper develops new error assessment methods to evaluate the performance of debt sustainability analyses (DSAs) for low-income countries (LICs) from 2005-2015. We find some evidence of a bias towards optimism for public and external debt projections, which was most appreciable for LICs with the highest incomes, prospects for market access, and at 'moderate' risk of debt distress. This was often driven by overly-ambitious fiscal and/or growth forecasts, and projected 'residuals'. When we control for unanticipated shocks, we find that biases remain evident, driven in part by optimism regarding government fiscal reaction functions and expected growth dividends from investment.